Rhetorical Devices Used by Content Creators to Address the Boycott of the Game Dead by Daylight - Reynald Setyawan; Samuel Gunawan (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
This study was conducted to analyze the rhetorical devices used by Otzdarva, an affiliated content creator to Behaviour Interactive Inc., and Scott Jund, an unaffiliated content creator, to address the boycott of the game Dead by Daylight. In addition, the writer observed the similarities and differences in the rhetorical devices used by both content creators. In conducting the study, the writer used the rhetorical devices theory by Harris (2018) and the audience design model by Bell (1984, as cited in Seargeant and Tagg, 2014). This study was done using a descriptive qualitative approach. The findings show that Otzdarva used all rhetorical devices from the transition category and five rhetorical devices from the restatement category, while Scott Jund used all rhetorical devices from the transition category and six rhetorical devices from the restatement category. This study showed that the difference in audience roles creates differences in how content creators use rhetorical devices.